Effects of photoperiod, plant growth regulators and culture media on in vitro growth of seedlings of Cyrtochilum loxense (Lindl.) Kraenzl. an endemic and endangered orchid from Ecuador - González, Yadira (2014)
Cyrtochilum loxense (Lindl.) Kraenzl. is an endemic and seriously endangered orchid species endemic in the Loja Province (Southern Ecuador). The main goals of this research were to analyze how culture media, plant growth regulators and photoperiod affect the growth of C. loxense. Eight month old plants (approximate 1 – 1.5 cm in height) obtained by in vitro germination, were cultivated on MS media or Knudson C; MS with three levels of naphthalene acetic acid (NAA) and 6-benzylaminopurine (BAP) (2/0.5; 1/0.5 y 0.5/ 0.5 mg-1L); and three photoperiodic regimes (24/0, 16/8, 8/16 h) on MS with and without plant growth regulators. No significant differences of shoot induction were observed on media with or without plant growth regulators, and all tested photoperiods. The highest growth (1.2 cm) was observed in plantlets cultivated on growth regulator-free media with a 16/8 photoperiod. Also the shoot and root formation was better in this species in absence of plant growth regulators. Probably this response is due to the endogenous hormone levels in the tissues or due to the kind and concentrations of PGRs used were too low to induce positive morphogenetic responses.